Ultrasound-Guided Regional Anaesthesia in the Paediatric Population. (18th June 2012) - Gerrard, Catherine; Roberts, Steve
Abstract : Ultrasound-guided regional anaesthesia is rapidly growing in popularity. Initially, most evidence was for the benefits when used in adults, but there is now a multitude of well-documented benefits in children. The practice of regional anaesthesia in children differs somewhat from that of adults in that in the majority of cases it is used for analgesia and performed under general anaesthesia to allow placement, rather than alone for anaesthesia as in adults. The purpose of this paper is to review the basic aspects of ultrasound regional anaesthesia before going into detail regarding specific techniques.